ENDOGENOUS HORMONE CONCENTRATIONS IN EXPLANTS AND CALLUSES OF BITTER MELON (Momordica charantia L.) - Y. Tang (Interciencia, 2010)
Anthers and stems of bitter melon (Momordica charantia L.) cv Bixiu were used for in vitro culture establishment. The endogenous hormone concentrations (indoleacetic acid (IAA), abscisic acid (ABA), gibberellins 3 (GA3), and zeatin (ZT)) of the initial explants and calluses were determined by means of high pressure liquid chromatography (HPLC). The endogenous IAA and IAA/ZT ratio were higher in the explants that were more effective to induce callus, and ABA was negative to callus formation. When analyzing the endogenous hormone concentrations in the various callus types generated in anthers and stems, it was found that a higher concentrations of ZT was present in the stem calluses that had formed buds, while higher IAA/ZT and GA3/ZT ratios were present in the calluses having no bud formation capacity, originated from anthers and stems.